Anti-apoptogenic function of TGFβ1 for human synovial cells: TGFβ1 protects cultured synovial cells from mitochondrial perturbation induced by several apoptogenic stimuli. Issue 1 (12th December 2003) - Kawakami, A; Urayama, S; Yamasaki, S; Hida, A; Miyashita, T; Kamachi, M; Nakashima, K; Tanaka, F; Ida, H; Kawabe, Y; Aoyagi, T; Furuichi, I; et al.
Abstract : Objective: To investigate anti-apoptogenic mechanism of transforming growth factor β1 (TGFβ1) towards synovial cells. Methods: Isolated synovial cells, treated or not with TGFβ1, were cultured in the presence or absence of anti-Fas IgM, proteasome inhibitor Z-Leu-Leu-Leu-aldehyde (LLL-CHO), etoposide, or C2-ceramide. After cultivation, apoptosis of synovial cells was examined by the presence of hypodiploid DNA + cells, the presence of terminal deoxy (d)-UTP nick end labelling + cells (TUNEL + cells), activation of caspases, and disruption of mitochondrial transmembrane potential (ΔΨm). Results: Activation of caspase-9 and ΔΨm was found in anti-Fas IgM treated synovial cells. The increment of both hypodiploid DNA + cells and TUNEL + cells accompanied by the activation of caspase-8 and caspase-3 was also determined in anti-Fas IgM treated synovial cells. These hallmarks for apoptosis induced by anti-Fas IgM were significantly suppressed in TGFβ1 treated synovial cells. LLL-CHO, etoposide, and C2-ceramide also caused ΔΨm, the increment of both hypodiploid DNA + cells and TUNEL + cells, and the activation of both Leu-Glu-His-Asp ase (LEHDase; caspase-9 like activity) and Asp-Glu-Val-Asp ase (DEVDase; caspase-3 like activity) in synovial cells. As determined in anti-Fas IgM treatment, TGFβ1 significantly reduced apoptotic cell death of synovial cells induced by the above chemicals. Conclusions: The protective effect of TGFβ1 for mitochondrial homoeostasis may be important in the anti-apoptogenic function of TGFβ1 for synovial cells.